Temporal Discounting in Later Life - Ellam Kulati; Michal Myck; Giacomo Pasini (Institute of Labor Economics (IZA), 2022)
We explore intertemporal decision-making in later life by looking at temporal preference heterogeneity among older individuals. Using choice tasks responses from Poland collected as part of the Survey of Health, Ageing, and Retirement in Europe (SHARE), we elicit individual time preferences using competing discounting specifications. With the formulation that best fits our data, we examine which individual characteristics drive the estimated heterogeneity in later life time preferences. Individual numerical abilities, labour and marital status, as well as household income turn out to be significant correlates of patience. Our analysis also provides methodological guidance for instrument design with the aim of eliciting time preferences in a general survey setting.
Keywords: D12; D15; C83; J14; 330; time preferences; discount rate; present bias; survey methodology; old age